Dinosaur train. Classic in the Jurassic [videorecording (DVD)] (The Jim Henson Company, 2014)
The Pteranodon family is super excited to be traveling to the 'Classic in the Jurassic,' an Olympics type competition in which different dinosaur teams representing the three Mesozoic time periods will compete in various contests.